Polycarbonate resin composition and molded article thereof

By using formate-based modified polysiloxane and aromatic environmentally friendly carbonate-polysiloxane copolymer in aromatic environmentally friendly carbonate resins, the insufficient sliding performance of the resin and the appearance of the mold are solved, and the effects of high wear resistance and low friction coefficient are achieved, and environmental pollution of fluoride-based sliders are avoided.

JP7670532B2Active Publication Date: 2025-04-30TEIJIN LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021064627
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-04-06
Publication Date
2025-04-30
Estimated Expiration
2041-04-06

AI Technical Summary

Technical Problem

While improving the sliding performance of aromatic environmentally friendly carbonate resin, it is difficult to maintain a good mold appearance, avoid layer separation, and the use of fluoride-based sliders will cause environmental pollution.

Method used

A carbonate resin synthesis system consisting of formate-based modified polyorganosiloxane and aromatic environmentally friendly carbonate-polydiorganosiloxane copolymer is used to improve the wear resistance and friction coefficient of the resin by adjusting the composition and structure of the copolymer, while avoiding layer separation.

Benefits of technology

It is achieved that the wear resistance of the carbonate resin is significantly improved and the friction coefficient is reduced while maintaining a good mold appearance and avoiding layer separation without the use of fluoride-based sliders.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007670532000001
    Figure 0007670532000001
  • Figure 0007670532000002
    Figure 0007670532000002
  • Figure 0007670532000003
    Figure 0007670532000003
Patent Text Reader

Abstract

To provide a polycarbonate resin composition that maintains a good molding appearance with suppressed layer separation, while having dramatically improved wear resistance without using a fluorine-based slide agent, and also having a reduced frictional coefficient, and a molding thereof.SOLUTION: The present invention discloses a polycarbonate resin composition. Relative to 100 pts.wt. of (A) a resin component (A component) comprising (A-1) a polycarbonate-polydiorganosiloxane copolymer 1-100 pts.wt., which comprises an aromatic polycarbonate block and a polydiorganosiloxane block represented by the general formula [3], and (A-2) an aromatic polycarbonate resin 0-99 pts.wt., the polycarbonate resin composition comprises (B) a methacryl-modified polyorganosiloxane (B component) 3.0-15.0 pts.wt.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polycarbonate resin composition and a molded article. More specifically, the present invention relates to a polycarbonate resin composition and a molded article that use a specific (meth)acrylic-modified polyorganosiloxane and a polycarbonate-polydiorganosiloxane copolymer, thereby suppressing layer separation and maintaining a good molded appearance, and that has dramatically improved wear resistance and a reduced friction coefficient without using a fluorine-based sliding agent. [Background technology]

[0002] Aromatic polycarbonate resins have many excellent material properties, and therefore various products are made using simple and highly productive processing methods such as injection molding, and are used in a very wide range of industrial fields. In particular, in the fields of office automation equipment and electrical and electronic equipment, aromatic polycarbonate resins, which have excellent dimensional accuracy, mechanical strength, and heat resistance, are increasingly used for sliding members such as gears in order to reduce the size and weight of the equipment and the number of parts. However, when polycarbonate resins are used alone, the sliding properties are insufficient, and there is a demand for improving the sliding properties. For example, it has been disclosed that resins such as polytetrafluoroethylene, polyolefin, polyamide, and polyester are added to polycarbonate resins as sliding property improvers (see Patent Documents 1 and 2). However, when polytetrafluoroethylene resins are blended with polycarbonate resins, problems arise in that molding processability and impact strength are reduced. Furthermore, halogen compounds such as polytetrafluoroethylene resin generate hydrofluoric acid when molded articles containing them are incinerated as waste, and therefore their use is currently being discouraged, just like organic halogen-based flame retardants. In response to the increasing demand for environmentally friendly materials, there is a demand for sliding materials that do not use fluorine-based sliding agents such as polytetrafluoroethylene resin.

[0003] Furthermore, if a sliding agent such as polyolefin, polyamide, or polyester is used, not only will it be impossible to obtain sliding properties equivalent to those of a fluorine-based sliding agent, but the inherent properties of polycarbonate resin, such as mechanical strength, heat resistance, and flame retardancy, will be impaired.

[0004] On the other hand, it has also been disclosed that silicone oil, which is a chemically and physically stable lubricant, is added to polycarbonate resin (see Patent Document 3). However, since the silicone oil on the surface of the molded product seeps out and is consumed in a short time, although excellent sliding properties are exhibited in the early stages, the long-term sliding properties are insufficient, and there are also problems such as the surface being sticky, which are not satisfactory. In addition, in order to obtain sufficient sliding properties, a large amount of silicone oil must be added, and as a result, the silicone oil is likely to separate into phases on the surface of the molded product, resulting in uneven gloss and other problems, which are not satisfactory in practical use. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Publication No. 63-213555 [Patent Document 2] Japanese Patent Application Publication No. 4-136065 [Patent Document 3] Special Publication No. 36-7641 Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to provide a polycarbonate resin composition and a molded article which have dramatically improved abrasion resistance and a reduced coefficient of friction without using a fluorine-based sliding agent, while maintaining a good molded appearance with suppressed layer separation. [Means for solving the problem]

[0007] As a result of extensive investigations aimed at solving the above problems, the present inventors discovered that the above problems can be solved by the following configuration, and arrived at the present invention.

[0008] (Configuration 1) (A) A polycarbonate resin composition comprising 100 parts by weight of a resin component (A component) consisting of (A-1) 1 to 100 parts by weight of a polycarbonate-polydiorganosiloxane copolymer consisting of a polycarbonate block represented by the following general formula [1] and a polydiorganosiloxane block represented by the following general formula [3], and (A-2) 0 to 99 parts by weight of an aromatic polycarbonate resin consisting of a polycarbonate block represented by the following general formula [1], and (B) 3.0 to 15.0 parts by weight of a (meth)acrylic-modified polyorganosiloxane (B component).

[0009] [ka]

[0010] [(In the above general formula [1], R 1 and R 2 each independently represents a group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 18 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 14 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxy group, and when there are a plurality of each of these groups, they may be the same or different, e and f each represent an integer of 1 to 4, and W represents a single bond or at least one group selected from the group consisting of groups represented by the following general formula [2]:

[0011] [ka]

[0012] (In the above general formula [2], R11 ,R 12 ,R 13 ,R 14 ,R 15 ,R 16 ,R 17 and R 18 each independently represents a group selected from the group consisting of a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, an aryl group having 6 to 14 carbon atoms, and an aralkyl group having 7 to 20 carbon atoms; R 19 and R 20 each independently represents a group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 10 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxy group, and when there are a plurality of groups, they may be the same or different, g is an integer from 1 to 10, and h is an integer from 4 to 7.)

[0013] [ka]

[0014] (In the above general formula [3], R 3 , R 4 , R 5 , R 6 , R 7 and R 8 are each independently a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 12 carbon atoms; R 9 and R 10 are each independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms, p is a natural number, q is 0 or a natural number, and the average chain length p+q is a natural number of 20 to 200. X is a divalent aliphatic group having 2 to 8 carbon atoms.

[0015] (Configuration 2) The polycarbonate resin composition according to the above-mentioned configuration 1, characterized in that p+q in the above-mentioned formula [3] is 30 to 120. (Configuration 3) 3. The polycarbonate resin composition according to configuration 1 or 2, wherein the content of the polydiorganosiloxane block represented by the above formula [3] in component A-1 is 4 to 20% by weight. (Configuration 4) 4. The polycarbonate resin composition according to any one of the above configurations 1 to 3, wherein the viscosity average molecular weight of component A-1 is 11,000 to 30,000. (Configuration 5) The polycarbonate resin composition according to any one of the above structures 1 to 4, characterized in that the polydiorganosiloxane block represented by the above formula [3] is a polydiorganosiloxane block derived from a (2-allylphenol)-terminated polydiorganosiloxane or a (2-methoxy-4-allylphenol)-terminated polydiorganosiloxane. (Configuration 6) R in the above formula [3] 3 , R 4 , R 5 , R 6 , R 7 and R 8 The polycarbonate resin composition according to any one of the above configurations 1 to 5, wherein is a methyl group. (Configuration 7) 7. The polycarbonate resin composition according to any one of the above configurations 1 to 6, wherein the polycarbonate block represented by the above formula [1] is a polycarbonate block derived from 2,2-bis(4-hydroxyphenyl)propane. (Configuration 8) The polycarbonate resin composition according to any one of the above structures 1 to 7, characterized in that component B is a (meth)acrylic-modified polyorganosiloxane obtained by graft copolymerizing a (meth)acrylic acid ester (component B2) with a polyorganosiloxane (component B1) represented by the following general formula [4]:

[0016] [ka]

[0017] [In the above general formula [4], R 1 , R 2 and R 3 each independently represents a hydrocarbon group having 1 to 20 carbon atoms or a halogenated hydrocarbon group having 1 to 20 carbon atoms, and Y represents an organic group having at least one group selected from the group consisting of a vinyl group, an allyl group, and a γ-(meth)acryloxypropyl group, and an SH group. 1 and X 2 each independently represents a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, or SiR 4 R 5 R 6 (R 4 , R 5 each independently represents a hydrocarbon group having 1 to 20 carbon atoms or a halogenated hydrocarbon group having 1 to 20 carbon atoms; R 6 represents an organic group having at least one group selected from the group consisting of a hydrocarbon group having 1 to 20 carbon atoms, a halogenated hydrocarbon group having 1 to 20 carbon atoms, or a radical reactive group selected from the group consisting of a vinyl group, an allyl group, and a γ-(meth)acryloxypropyl group, and an SH group), m is an integer of 1 to 10,000, n is an integer of 1 or more, and the siloxane chain may be branched.]

[0018] (Configuration 9) In the above formula [4], R 1 ,R 2 ,R 3 9. The polycarbonate resin composition according to the above-mentioned configuration 8, wherein is a methyl group. (Configuration 10) 10. The polycarbonate resin composition according to claim 8 or 9, wherein component B2 is methyl methacrylate and / or 2-hydroxyethyl methacrylate. (Configuration 11) 11. A molded article formed from the polycarbonate resin composition according to any one of claims 1 to 10. Effect of the Invention

[0019] The polycarbonate resin composition of the present invention is a polycarbonate resin composition that has dramatically improved abrasion resistance and a reduced friction coefficient without using a fluorine-based sliding agent, while maintaining a good molded appearance with suppressed layer separation. Therefore, the composition is useful for internal mechanism parts of electric and electronic devices, office equipment, and the like, which are particularly required to be environmentally friendly, and its industrial usefulness is extremely great. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] (Component A: resin component) The resin component of the present invention comprises 1 to 100 parts by weight of a polycarbonate-polydiorganosiloxane copolymer (A-1) and 0 to 99 parts by weight of an aromatic polycarbonate resin (A-2).

[0021] (A-1 component: polycarbonate-polydiorganosiloxane copolymer) In the present invention, the polycarbonate-polydiorganosiloxane copolymer (hereinafter sometimes abbreviated as PC-POS copolymer) is a polycarbonate-polydiorganosiloxane copolymer consisting of a polycarbonate block represented by formula [1] and a polydiorganosiloxane block represented by formula [3].

[0022] <Polycarbonate block represented by formula [1]> In the present invention, the polycarbonate block is represented by the following formula [1].

[0023] [ka]

[0024] In the above formula [1], R 1 and R 2each independently represents a group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 18 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 14 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxy group, and when there are a plurality of each, they may be the same or different.

[0025] Examples of halogen atoms include fluorine, chlorine, and bromine atoms. Examples of alkyl groups having 1 to 18 carbon atoms include methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, dodecyl, and tetradecyl groups. Preferred are alkyl groups having 1 to 6 carbon atoms. Examples of alkoxy groups having 1 to 18 carbon atoms include methoxy, ethoxy, propoxy, butoxy, pentoxy, hexoxy, and octoxy groups. Preferred are alkoxy groups having 1 to 6 carbon atoms. Examples of cycloalkyl groups having 6 to 20 carbon atoms include cyclohexyl and cyclooctyl groups. Preferred are cycloalkyl groups having 6 to 12 carbon atoms. Examples of cycloalkoxy groups having 6 to 20 carbon atoms include cyclohexyloxy and cyclooctyloxy groups. Preferred are cycloalkyl groups having 6 to 12 carbon atoms. Examples of the alkenyl group having 2 to 10 carbon atoms include a methenyl group, an ethenyl group, a propenyl group, a butenyl group, and a pentenyl group. An alkenyl group having 2 to 6 carbon atoms is preferable. Examples of the aryl group having 6 to 14 carbon atoms include a phenyl group and a naphthyl group. Examples of the aryloxy group having 6 to 14 carbon atoms include a phenyloxy group and a naphthyloxy group. Examples of the aralkyl group having 7 to 20 carbon atoms include a benzyl group and a phenylethyl group. Examples of the aralkyloxy group having 7 to 20 carbon atoms include a benzyloxy group and a phenylethyloxy group.

[0026] e and f each independently represents an integer of 1 to 4.

[0027] W is a single bond or at least one group selected from the group consisting of groups represented by the following formula [2]:

[0028] [ka]

[0029] In the above formula [2], R 11 , R 12 , R 13 , R 14 , R 15 , R 16 , R 17 and R 18 each independently represents a group selected from the group consisting of a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, an aryl group having 6 to 14 carbon atoms, and an aralkyl group having 7 to 20 carbon atoms.

[0030] Examples of the alkyl group having 1 to 18 carbon atoms include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, a heptyl group, an octyl group, a nonyl group, a decyl group, and a dodecyl group. An alkyl group having 1 to 6 carbon atoms is preferable. Examples of the aryl group having 6 to 14 carbon atoms include a phenyl group, a naphthyl group, and the like. These may be substituted. Examples of the substituent include an alkyl group having 1 to 6 carbon atoms, such as a methyl group, an ethyl group, a propyl group, and a butyl group. Examples of the aralkyl group having 7 to 20 carbon atoms include a benzyl group, a phenylethyl group, and the like.

[0031] R 19 and R 20each independently represents a group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 10 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxy group, and when there are a plurality of such groups, they may be the same or different.

[0032] Examples of halogen atoms include fluorine, chlorine, and bromine atoms. Examples of alkyl groups having 1 to 18 carbon atoms include methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, dodecyl, and tetradecyl groups. Preferred are alkyl groups having 1 to 6 carbon atoms. Examples of alkoxy groups having 1 to 10 carbon atoms include methoxy, ethoxy, propoxy, butoxy, and pentoxy groups. Preferred are alkoxy groups having 1 to 6 carbon atoms. Examples of cycloalkyl groups having 6 to 20 carbon atoms include cyclohexyl and cyclooctyl groups. Preferred are cycloalkyl groups having 6 to 12 carbon atoms. Examples of cycloalkoxy groups having 6 to 20 carbon atoms include cyclohexyloxy and cyclooctyl groups. Preferred are cycloalkyl groups having 6 to 12 carbon atoms. Examples of the alkenyl group having 2 to 10 carbon atoms include a methenyl group, an ethenyl group, a propenyl group, a butenyl group, and a pentenyl group. An alkenyl group having 2 to 6 carbon atoms is preferable. Examples of the aryl group having 6 to 14 carbon atoms include a phenyl group and a naphthyl group. Examples of the aryloxy group having 6 to 14 carbon atoms include a phenyloxy group and a naphthyloxy group. Examples of the aralkyl group having 7 to 20 carbon atoms include a benzyl group and a phenylethyl group. Examples of the aralkyloxy group having 7 to 20 carbon atoms include a benzyloxy group and a phenylethyloxy group.

[0033] g is an integer of 1 to 10, preferably an integer of 1 to 6. h is an integer of 4 to 7, preferably an integer of 4 to 5.

[0034] The polycarbonate block represented by the formula [1] is preferably a polycarbonate block derived from 2,2-bis(4-hydroxyphenyl)propane.

[0035] The length of the polycarbonate block is preferably 10 to 100, more preferably 30 to 100, and even more preferably 50 to 70, in terms of the average number of repeating units of the formula [1].

[0036] The content of the polycarbonate block represented by the formula [1] is preferably 50 to 99.9% by weight, more preferably 70 to 99.5% by weight, and even more preferably 80 to 99.0% by weight, based on the total weight of the copolymer.

[0037] <Polydiorganosiloxane block represented by formula [3]> In the present invention, the polydiorganosiloxane block is represented by the following formula [3].

[0038] [ka]

[0039] In the above formula [3], R 3 , R 4 , R 5 , R 6 , R 7 and R 8 each independently represents a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 12 carbon atoms.

[0040] Examples of the alkyl group having 1 to 12 carbon atoms include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, a heptyl group, an octyl group, a nonyl group, a decyl group, and a dodecyl group. An alkyl group having 1 to 6 carbon atoms is preferable. Examples of the substituted or unsubstituted aryl group having 6 to 12 carbon atoms include a phenyl group and a naphthyl group. Examples of the substituent include an alkyl group having 1 to 12 carbon atoms such as a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, and a hexyl group. R 3 , R 4 , R 5 , R 6 , R 7 and R 8 is preferably a methyl group.

[0041] R 9 and R 10 are each independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms.

[0042] Examples of halogen atoms include fluorine, chlorine, and bromine atoms. Examples of alkyl groups having 1 to 10 carbon atoms include methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, and dodecyl groups. Preferred are alkyl groups having 1 to 6 carbon atoms. Examples of alkoxy groups having 1 to 10 carbon atoms include methoxy, ethoxy, propoxy, butoxy, pentoxy, hexoxy, heptoxy, and octoxy groups. Preferred are alkoxy groups having 1 to 6 carbon atoms.

[0043] X is a divalent aliphatic group having 2 to 8 carbon atoms. The divalent aliphatic group may be an alkylene group having 2 to 8 carbon atoms. Examples of the alkylene group include an ethylene group, a trimethylene group, a tetramethylene group, and the like. Examples of the substituent include the aryl group.

[0044] The polydiorganosiloxane block represented by the above formula [3] is preferably a polydiorganosiloxane block derived from a (2-allylphenol)-terminated polydiorganosiloxane or a (2-methoxy-4-allylphenol)-terminated polydiorganosiloxane. That is, in formula [3], X is a trimethylene group and R 9 and R 10 is a hydrogen atom, or X is a trimethylene group and R 9 and R 10 is preferably a methoxy group.

[0045] The content of the polydiorganosiloxane block represented by the above formula [3] is preferably 4 to 20% by weight, more preferably 6 to 19% by weight, and even more preferably 8 to 18% by weight, based on the total weight of the polycarbonate-polydiorganosiloxane copolymer. If the content is less than the lower limit, the formation of maximum domains may be insufficient and low-temperature impact resistance may not be exhibited, while if the content is more than the upper limit, there may be major problems in terms of production, such as poor polymerization reaction due to deterioration of the emulsion state and difficulty in granulation due to an excessively low glass transition temperature.

[0046] The viscosity average molecular weight of the A-1 component is preferably 11,000 to 30,000, more preferably 13,000 to 25,000, further preferably 15,000 to 20,000, and particularly preferably 15,000 to 18,000. If the viscosity average molecular weight of the A-1 component is less than the lower limit, it may be difficult to obtain practical mechanical strength in many fields, and the kneadability may deteriorate due to a large difference in melt viscosity with the polycarbonate resin (A-2 component) to be mixed, and if it exceeds the upper limit, the melt viscosity is high and generally a high molding processing temperature is required, which may lead to problems such as thermal deterioration of the resin and a decrease in productivity due to poor separation in the water washing step during production.

[0047] p is a natural number, q is 0 or a natural number, and the average chain length p+q is a natural number of 20 to 200. The average chain length p+q is preferably a natural number of 30 to 120, and more preferably a natural number of 30 to 70.

[0048] (Aromatic polycarbonate resin (A-2)) The aromatic polycarbonate resin (A-2) in the present invention is derived from a dihydric phenol (I) represented by the general formula [5].

[0049] [ka]

[0050] (In the above general formula [5], R 1 , R 2 , e, f and W are the same as in equation [1].)

[0051] Examples of the dihydric phenol include 4,4'-dihydroxybiphenyl, bis(4-hydroxyphenyl)methane, 1,1-bis(4-hydroxyphenyl)ethane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(4-hydroxy-3-methylphenyl)propane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 2,2-bis(4-hydroxy-3,3'-biphenyl)propane, 2,2-bis(4-hydroxy- 3-isopropylphenyl)propane, 2,2-bis(3-t-butyl-4-hydroxyphenyl)propane, 2,2-bis(4-hydroxyphenyl)butane, 2,2-bis(4-hydroxyphenyl)octane, 2,2-bis(3-bromo-4-hydroxyphenyl)propane, 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)propane, 2,2-bis(3-cyclohexyl-4-hydroxyphenyl)propane, 1,1-bis(3-cyclohexyl-4-hydroxyphenyl)cyclohexane, bis(4-hydroxyphenyl) 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)cyclopentane, 4,4'-dihydroxydiphenyl ether, 4,4'-dihydroxy-3,3'-dimethyldiphenyl ether, 4,4'-sulfonyldiphenol, 4,4'-dihydroxydiphenyl sulfoxide, 4,4'-dihydroxydiphenyl sulfide, 2,2'-dimethyl -4,4'-sulfonyldiphenol, 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfoxide, 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfide, 2,2'-diphenyl-4,4'-sulfonyldiphenol, 4,4'-dihydroxy-3,3'-diphenyldiphenyl sulfoxide, 4,4'-dihydroxy-3,3'-diphenyldiphenyl sulfide, 1,3-bis{2-(4-hydroxyphenyl)propyl}benzene, 1,4-bis{2-(4-hydroxyphenyl)propyl}benzene, 1,Examples of the cyclohexane derivatives include 4-bis(4-hydroxyphenyl)cyclohexane, 1,3-bis(4-hydroxyphenyl)cyclohexane, 4,8-bis(4-hydroxyphenyl)tricyclo[5.2.1.02,6]decane, 4,4'-(1,3-adamantanediyl)diphenol, and 1,3-bis(4-hydroxyphenyl)-5,7-dimethyladamantane.

[0052] Among these, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(4-hydroxy-3-methylphenyl)propane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 4,4'-sulfonyldiphenol, 2,2'-dimethyl-4,4'-sulfonyldiphenol, 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, 1,3-bis{2-(4-hydroxyphenyl)propyl}benzene, and 1,4-bis{2-(4-hydroxyphenyl)propyl}benzene are preferred, and 2,2-bis(4-hydroxyphenyl)propane, 1,1-bis(4-hydroxyphenyl)cyclohexane (BPZ), 4,4'-sulfonyldiphenol, and 9,9-bis(4-hydroxy-3-methylphenyl)fluorene are particularly preferred. Among these, 2,2-bis(4-hydroxyphenyl)propane, which has excellent strength and good durability, is most suitable. These may be used alone or in combination of two or more kinds.

[0053] The component A of the present invention is composed of 100-1 parts by weight of polycarbonate-polydiorganosiloxane copolymer (A-1) and 0-99 parts by weight of aromatic polycarbonate resin (A-2), preferably 90-5 parts by weight of component A-1 and 10-95 parts by weight of component A-2, more preferably 60-10 parts by weight of component A-1 and 40-90 parts by weight of component A-2. If the component A-1 is less than 1 part by weight, the components A and B are not sufficiently compatible, resulting in surface peeling and poor marbled appearance, and the surface peeling is likely to cause scraping, which also deteriorates wear resistance.

[0054] The viscosity average molecular weight of component A is preferably 11,000 to 30,000, more preferably 12,000 to 25,000. If it is less than 11,000, sufficient toughness may not be maintained and it may not be suitable for practical use. If it is more than the upper limit, the solution viscosity may increase, resulting in reduced productivity and insufficient molding flowability.

[0055] (Polydiorganosiloxane) In the present invention, a polydiorganosiloxane having a specific average chain length and represented by the following general formula [6], hydroxyaryl-terminated polydiorganosiloxane (II), is used as a raw material.

[0056] [ka]

[0057] (In the above general formula [6], R 3 , R 4 , R 5 , R 6 , R 7 and R 8 are each independently a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 12 carbon atoms; R 9 and R 10 are each independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms, p is a natural number, q is 0 or a natural number, and the average chain length p+q is a natural number of 20 to 200. X is a divalent aliphatic group having 2 to 8 carbon atoms.

[0058] The average chain length p+q is preferably a natural number of 30 to 120, more preferably a natural number of 30 to 70. In order to satisfy such a specific chain length range, two or more different hydroxyaryl-terminated polydiorganosiloxane (II) raw materials having an average chain length p+q may be mixed to prepare the polydiorganosiloxane. In that case, it is preferable to use a polydiorganosiloxane (E-1) having an average chain length p+q of 1 or more and less than 60 and a polydiorganosiloxane (E-2) having an average chain length p+q of 60 or more and 200 or less as raw materials. The polydiorganosiloxane raw material may be mixed by mixing appropriate polydiorganosiloxane raw materials whose ends have been hydroxyaryl-modified, or by mixing polydiorganosiloxane precursors having an appropriate average chain length before the ends are hydroxyaryl-modified, and then modifying the ends with hydroxyaryl. The average chain length p+q is calculated by nuclear magnetic resonance (NMR) measurement.

[0059] When the polydiorganosiloxane (E-1) and the polydiorganosiloxane (E-2) are mixed, they are preferably used in a weight ratio of (E-1):(E-2)=1:99 to 99:1, and more preferably 10:90 to 90:10.

[0060] It is more preferable to use, as the polydiorganosiloxane raw material, polydiorganosiloxane (E) obtained by previously blending the above-mentioned polydiorganosiloxanes (E-1) and (E-2). The blending ratio, similar to the above-mentioned (E-1):(E-2) (weight ratio), is preferably 1:99 to 99:1, more preferably 10:90 to 90:10.

[0061] When blended in advance, the lower limit of the average chain length p+q of the polydiorganosiloxane (E-1) is preferably 1 or more, more preferably 20 or more, and even more preferably 30 or more, and the upper limit is preferably less than 60, more preferably less than 50, and even more preferably less than 45. The lower limit of the average chain length p+q of the polydiorganosiloxane (E-2) is preferably 60 or more, more preferably 70 or more, and even more preferably 90 or more, and the upper limit is preferably 200 or less, and more preferably 100 or less. As the hydroxyaryl-terminated polydiorganosiloxane (II) represented by the general formula [6], for example, the following compounds are preferably used.

[0062] [ka]

[0063] Hydroxyaryl-terminated polydiorganosiloxane (II) is a phenol having an olefinic unsaturated carbon-carbon bond, and is easily produced by subjecting vinylphenol, 2-allylphenol, isopropenylphenol, or 2-methoxy-4-allylphenol to a hydrosilylation reaction at the end of a polysiloxane chain having a predetermined degree of polymerization. Among these, (2-allylphenol)-terminated polydiorganosiloxane and (2-methoxy-4-allylphenol)-terminated polydiorganosiloxane are preferred, and (2-allylphenol)-terminated polydimethylsiloxane and (2-methoxy-4-allylphenol)-terminated polydimethylsiloxane are particularly preferred.

[0064] <Production method of polycarbonate-polydiorganosiloxane copolymer> The polycarbonate-polydiorganosiloxane copolymer of the present invention can be produced by the steps (i) and (ii).

[0065] (Step (i)) Step (i) is a step of reacting a dihydric phenol (I) represented by the following formula [5] with phosgene in a mixed solution of a water-insoluble organic solvent and an alkaline aqueous solution to prepare a solution containing a carbonate oligomer having a terminal chloroformate group.

[0066] [ka]

[0067] (In the formula, R 1 , R 2 , e, f and W are the same as above.)

[0068] The dihydric phenol (I) represented by the formula [5] is, for example, 1,1-bis(4-hydroxyphenyl)-1,1-diphenyl ether. Preferred are 2,2-bis(4-hydroxyphenyl)-1-phenylethane, 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(4-hydroxy-3-methylphenyl)propane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 4,4'-sulfonyldiphenol, 2,2'-dimethyl-4,4'-sulfonyldiphenol, 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, 1,3-bis{2-(4-hydroxyphenyl)propyl}benzene, and 1,4-bis{2-(4-hydroxyphenyl)propyl}benzene.

[0069] In particular, 2,2-bis(4-hydroxyphenyl)propane, 1,1-bis(4-hydroxyphenyl)cyclohexane (BPZ), 4,4'-sulfonyldiphenol, and 9,9-bis(4-hydroxy-3-methylphenyl)fluorene are preferred. Among them, 2,2-bis(4-hydroxyphenyl)propane, which has excellent strength and good durability, is most preferred. These may be used alone or in combination of two or more.

[0070] The PC-POS copolymer of the present invention can be produced by following the known production methods described in, for example, WO2011 / 013846 and WO2019 / 124556, but the following method is suitable when it is particularly desired to improve low-temperature impact resistance. In order to form coarse domains of 80 nm or more that improve low-temperature impact resistance, it is effective to react a polydiorganosiloxane at a high concentration with a carbonate oligomer having a terminal chloroformate group, which can produce a dispersion state that has not been seen before even in areas with a low content of siloxane blocks. Furthermore, as described above, a polydiorganosiloxane having a specific average chain length is used as a raw material, and only one type of hydroxyaryl-terminated polydiorganosiloxane (II) may be used, or two or more types may be used. Specifically, a raw material represented by the hydroxyaryl-terminated polydiorganosiloxane (II) represented by the above general formula [6] and having an average chain length p+q of 20 to 200 is used. In order to satisfy such a specific chain length range, two or more different types of hydroxyaryl-terminated polydiorganosiloxane (II) raw materials having an average chain length p+q may be mixed and used. In that case, it is preferable to use a polydiorganosiloxane (E-1) having an average chain length p+q of 1 or more and less than 60 and a polydiorganosiloxane (E-2) having an average chain length p+q of 60 or more and 200 or less as raw materials to prepare the polydiorganosiloxane, or to use a raw material obtained by premixing polydiorganosiloxane precursors having an appropriate average chain length before the terminals are modified with hydroxyaryls and then modifying the terminals with hydroxyaryls. Furthermore, the polydiorganosiloxane (E-1) and the polydiorganosiloxane (E-2) may be mixed in advance before reacting with the carbonate precursor and the dihydric phenol, or may be added to the reaction solution in parallel without being mixed in advance, or (E-1) and (E-2) may be divided and added successively to the reaction solution to react with the carbonate precursor and the dihydric phenol.More preferably, the polydiorganosiloxane (E-1) is added to the reaction solution, and then the polydiorganosiloxane (E-2) is added to the reaction solution to react with the carbonate precursor and dihydric phenol, which is advantageous in terms of efficiency and cost effectiveness due to simplification of the manufacturing process equipment. In either case, it is desirable to add the hydroxyaryl-terminated polydiorganosiloxane (II) to the reaction solution as quickly as possible, and it is preferable to add it all at once. The mass ratio of the polydiorganosiloxanes (E-1) and (E-2) used as raw materials is as described above, and the carbonate precursor and dihydric phenol will be described later.

[0071] In addition, comonomers other than the dihydric phenol (I) and hydroxyaryl-terminated polydiorganosiloxane (II) can be used in an amount of up to 10% by weight based on the total weight of the copolymer, provided that the use does not interfere with the production process of the present invention.

[0072] In the production method of the present invention, a mixed solution containing an oligomer having a terminal chloroformate group is prepared in advance by reacting a dihydric phenol (I) with a carbonate-forming compound in a mixed solution of a water-insoluble organic solvent and an aqueous alkaline solution.

[0073] In producing an oligomer of the dihydric phenol (I), the entire amount of the dihydric phenol (I) used in the method of the present invention may be converted into an oligomer at once, or a part of it may be added as a post-added monomer as a reaction raw material to the interfacial polycondensation reaction in the latter stage. The post-added monomer is added to quickly advance the polycondensation reaction in the latter stage, and there is no need to add it if it is not necessary.

[0074] The method of this oligomer formation reaction is not particularly limited, but it is usually preferable to carry out the reaction in a solvent in the presence of an acid binder.

[0075] The proportion of the carbonate ester-forming compound used may be appropriately adjusted in consideration of the stoichiometric ratio (equivalent) of the reaction. When a gaseous carbonate ester-forming compound such as phosgene is used, it is preferable to employ a method of blowing the gaseous compound into the reaction system.

[0076] As the acid binder, for example, an alkali metal hydroxide such as sodium hydroxide or potassium hydroxide, an alkali metal carbonate such as sodium carbonate or potassium carbonate, an organic base such as pyridine, or a mixture of these may be used.

[0077] The proportion of the acid binder used may be appropriately determined in consideration of the stoichiometric ratio (equivalent) of the reaction, as described above. Specifically, it is preferable to use 2 equivalents or a slightly excess amount of the acid binder relative to the number of moles of the dihydric phenol (I) used to form the oligomer (usually 1 mole corresponds to 2 equivalents).

[0078] As the solvent, a solvent inert to various reactions, such as those used in the production of known polycarbonates, may be used alone or as a mixed solvent. Representative examples include hydrocarbon solvents such as xylene, and halogenated hydrocarbon solvents such as methylene chloride and chlorobenzene. In particular, halogenated hydrocarbon solvents such as methylene chloride are preferably used.

[0079] The reaction pressure for oligomer formation is not particularly limited, and may be normal pressure, elevated pressure, or reduced pressure, but it is usually advantageous to carry out the reaction under normal pressure. The reaction temperature is selected from the range of -20 to 50°C, and in many cases, since heat is generated during polymerization, it is desirable to cool the reaction with water or ice. The reaction time depends on other conditions and cannot be specified in general, but is usually carried out for 0.2 to 10 hours.

[0080] The pH range of the oligomer formation reaction is similar to that of known interfacial reactions, and the pH is always adjusted to 10 or higher.

[0081] In the present invention, after obtaining a mixed solution containing an oligomer of dihydric phenol (I) having terminal chloroformate groups in this manner, the hydroxyaryl-terminated polydiorganosiloxane (II) is added to the dihydric phenol (I) while stirring the mixed solution, and the hydroxyaryl-terminated polydiorganosiloxane (II) and the oligomer are subjected to interfacial polycondensation to obtain a polycarbonate-polydiorganosiloxane copolymer.

[0082] When carrying out the interfacial polycondensation reaction, an acid binder may be appropriately added in consideration of the stoichiometric ratio (equivalent) of the reaction. Examples of the acid binder include alkali metal hydroxides such as sodium hydroxide and potassium hydroxide, alkali metal carbonates such as sodium carbonate and potassium carbonate, organic bases such as pyridine, and mixtures thereof. Specifically, the hydroxide to be used When the hydroxyaryl-terminated polydiorganosiloxane (II) or, as described above, a portion of the dihydric phenol (I) is added to this reaction stage as a post-added monomer, it is preferable to use 2 equivalents or an excess amount of alkali based on the total moles of the post-added dihydric phenol (I) and hydroxyaryl-terminated polydiorganosiloxane (II) (usually 1 mole corresponds to 2 equivalents).

[0083] The polycondensation by the interfacial polycondensation reaction between the oligomer of the dihydric phenol (I) and the hydroxyaryl-terminated polydiorganosiloxane (II) is carried out by vigorously stirring the above mixture.

[0084] In such a polymerization reaction, a terminal terminator or a molecular weight regulator is usually used. Examples of the terminal terminator include compounds having a monovalent phenolic hydroxyl group, such as ordinary phenol, p-tert-butylphenol, p-cumylphenol, tribromophenol, etc., as well as long-chain alkylphenols, aliphatic carboxylic acid chlorides, aliphatic carboxylic acids, hydroxybenzoic acid alkyl esters, hydroxyphenyl alkyl acid esters, and alkyl ether phenols. The amount of the terminal terminator is in the range of 100 to 0.5 mol, preferably 50 to 2 mol, relative to 100 mol of all dihydric phenol compounds used, and it is naturally possible to use two or more compounds in combination.

[0085] To accelerate the polycondensation reaction, a catalyst such as a tertiary amine, such as triethylamine, or a quaternary ammonium salt may be added.

[0086] The reaction time of the polymerization reaction needs to be relatively long in order to reduce the amount of unreacted polydiorganosiloxane components, preferably 30 minutes or more, more preferably 50 minutes or more, while stirring the reaction solution for a long period of time can cause polymer precipitation, so the reaction time is preferably 180 minutes or less, more preferably 90 minutes or less.

[0087] If desired, a small amount of an antioxidant such as sodium sulfite or hydrosulfide may be added.

[0088] The polycarbonate resin composition of the present invention can be made into a branched polycarbonate by using a branching agent in combination with the above-mentioned dihydric phenol compound. Examples of the trifunctional or higher polyfunctional aromatic compounds used in such branched polycarbonate resins include phloroglucin, phloroglucide, 4,6-dimethyl-2,4,6-tris(4-hydroxyphenyl)heptene-2,2,4,6-trimethyl-2,4,6-tris(4-hydroxyphenyl)heptane, 1,3,5-tris(4-hydroxyphenyl)benzene, 1,1,1-tris(4-hydroxyphenyl)ethane, 1,1,1-tris(3,5-dimethyl-4-hydroxyphenyl)ethane, 2,6-bis(2-hydroxy-5-methylbenzyl)-4-methylphenol, 4-{4-[1,1-bis(4- Examples of the trisphenols include trisphenols such as 1,4-dimethylbenzylphenol, tetra(4-hydroxyphenyl)methane, bis(2,4-dihydroxyphenyl)ketone, 1,4-bis(4,4-dihydroxytriphenylmethyl)benzene, trimellitic acid, pyromellitic acid, benzophenonetetracarboxylic acid, and acid chlorides thereof. Among these, 1,1,1-tris(4-hydroxyphenyl)ethane and 1,1,1-tris(3,5-dimethyl-4-hydroxyphenyl)ethane are preferred, and 1,1,1-tris(4-hydroxyphenyl)ethane is particularly preferred.

[0089] The reaction pressure may be reduced, normal, or increased, but is usually suitable for carrying out the reaction at normal pressure or the reaction system's own pressure. The reaction temperature is selected from the range of -20 to 50°C, and in many cases, since heat is generated during polymerization, it is desirable to cool the reaction system with water or ice. The reaction time depends on the reaction temperature, etc. It is not possible to specify a general time because it depends on other conditions, but it is usually performed for 0.5 to 10 hours.

[0090] In some cases, the obtained polycarbonate copolymer is subjected to a suitable physical treatment (mixing, fractionation, etc.) and / or chemical treatment (polymer reaction, crosslinking treatment, partial decomposition treatment, etc.) to obtain a desired reduced viscosity [η SPIt can also be obtained as a polycarbonate copolymer of [(1,2-dichlorophenyl)-1,2-difluorophenyl] and [(1,2-dichlorophenyl)-1,2-difluorophenyl].

[0091] The resulting reaction product (crude product) can be subjected to various post-treatments such as known separation and purification methods to recover a polycarbonate-polydiorganosiloxane copolymer of the desired purity (degree of purification).

[0092] (Component B: (meth)acrylic modified polyorganosiloxane) The resin composition of the present invention contains a (meth)acrylic-modified polyorganosiloxane as component B. The (meth)acrylic-modified polyorganosiloxane may also be called a silicone-modified (meth)acrylic polymer. The (meth)acrylic-modified polyorganosiloxane of the present invention is preferably a (meth)acrylic-modified polyorganosiloxane obtained by graft copolymerizing a (meth)acrylic acid ester (component B2) with a polyorganosiloxane (component B1) represented by the following general formula [4].

[0093] [ka]

[0094] [In the above general formula [4], R 1 , R 2 and R 3 each independently represents a hydrocarbon group having 1 to 20 carbon atoms or a halogenated hydrocarbon group having 1 to 20 carbon atoms, and Y represents an organic group having at least one group selected from the group consisting of a vinyl group, an allyl group, and a γ-(meth)acryloxypropyl group, and an SH group. 1 and X 2 each independently represents a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, or SiR 4 R 5 R 6 (R 4 , R 5 each independently represents a hydrocarbon group having 1 to 20 carbon atoms or a halogenated hydrocarbon group having 1 to 20 carbon atoms; R 6represents an organic group having at least one group selected from the group consisting of a hydrocarbon group having 1 to 20 carbon atoms, a halogenated hydrocarbon group having 1 to 20 carbon atoms, or a radical reactive group selected from the group consisting of a vinyl group, an allyl group, and a γ-(meth)acryloxypropyl group, and an SH group), m is an integer of 1 to 10,000, n is an integer of 1 or more, and the siloxane chain may be branched.]

[0095] In the above general formula [4], R 1 , R 2 and R 3 are preferably each independently a hydrocarbon group having 1 to 10 carbon atoms, and more preferably a methyl group.

[0096] Such (meth)acrylic modified polyorganosiloxanes can be produced by known methods. For example, they can be produced by combining hydrolysis, polymerization, and equilibration means using linear or cyclic low molecular weight polyorganosiloxanes or alkoxysilanes having the above groups. Hydrolysis, polymerization, and equilibration can be carried out by known techniques even in a state dispersed in water.

[0097] B2 is an alkyl ester of acrylic acid or methacrylic acid, or a hydroxyalkyl ester. Examples of such esters include esters and alkoxyalkyl esters, and specifically include acrylic esters such as methyl acrylate, ethyl acrylate, isopropyl acrylate, n-propyl acrylate, n-butyl acrylate, isobutyl acrylate, 2-ethylhexyl acrylate, isooctyl acrylate, n-octyl acrylate, 2-hydroxyethyl acrylate, and 2-methoxyethyl acrylate, and methacrylic esters such as methyl methacrylate, ethyl methacrylate, isopropyl methacrylate, n-propyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, n-hexyl methacrylate, 2-ethylhexyl methacrylate, n-lauryl methacrylate, 2-hydroxyethyl methacrylate, and 2-ethoxyethyl methacrylate. These can be used alone or in combination of two or more, and in particular, methyl methacrylate and 2-hydroxyethyl methacrylate are preferred.

[0098] In addition, other monomers copolymerizable with (meth)acrylic acid esters may be included. As representative examples of such monomers, there may be mentioned styrene-based compounds such as styrene, vinyl toluene, and α-methylstyrene, unsaturated nitriles such as acrylonitrile and methacrylonitrile, halogenated olefins such as vinyl chloride and vinylidene chloride, vinyl esters such as vinyl acetate and vinyl propionate, unsaturated amides such as acrylamide, methacrylamide, and N-methylolacrylamide, unsaturated carboxylic acids such as acrylic acid, methacrylic acid, and maleic anhydride, and other monomers having one double bond, as well as polyunsaturated monomers such as ethylene glycol dimethacrylate, propylene glycol dimethacrylate, 1,4-butanediol dimethacrylate, allyl methacrylate, triallyl cyanurate, and triallyl isocyanurate. Two or more of these may be used.

[0099] The content of these other copolymerizable monomers is preferably 30% by weight or less, more preferably 25% by weight or less, and even more preferably 20% by weight or less, based on the total amount with the (meth)acrylic acid ester being 100% by weight.

[0100] The graft copolymerization can be carried out by a known technique. For example, the polyorganosiloxane and the (meth)acrylic acid ester or a mixture of the polyorganosiloxane and other monomers are emulsified and dispersed in water, and polymerized in the presence of a radical polymerization initiator to carry out the graft copolymerization. The emulsifier and radical polymerization initiator used in this method may be known for emulsion polymerization. After the polymerization is completed, the graft copolymer can be obtained by salting out, filtering, washing with water, and drying. In this emulsion graft copolymerization, if the polyorganosiloxane is produced in a dispersed state in water as described above, the obtained emulsion of polyorganosiloxane can be used as it is as a raw material for graft copolymerization.

[0101] The (meth)acrylic modified polyorganosiloxane of the present invention is a graft copolymer of polyorganosiloxane (B1 component) and (meth)acrylic acid ester (B2 component) at a weight ratio of B1 component / B2 component of preferably 95 / 5 to 5 / 95, more preferably 90 / 10 to 20 / 80, further preferably 85 / 15 to 30 / 70, and particularly preferably 80 / 20 to 40 / 60. In this weight ratio, if the polyorganosiloxane exceeds 95 parts by weight, the compatibility with polycarbonate may be insufficient, resulting in poor mechanical strength, and if it is less than 5 parts by weight, the occurrence of black discoloration and poor appearance due to black spots may not be suppressed.

[0102] As an example of the acrylic modified polyorganosiloxane in the present invention, "Nissin Chemical Industry Co., Ltd. Common examples include "Chaline (trade name)" manufactured by Toa Gosei Co., Ltd., "Simac (trade name)" manufactured by Shin-Etsu Chemical Co., Ltd., "KP-578, KP-561P, KP-562P, etc. manufactured by Shin-Etsu Chemical Co., Ltd., "8BS" manufactured by Taisei Fine Chemical Co., Ltd., and "Zemlac (trade name) and Silyl (trade name)" manufactured by Kaneka Corporation.

[0103] The content of component B is 3.0 to 15.0 parts by weight, preferably 4.0 to 13.5 parts by weight, and more preferably 5.0 to 12.0 parts by weight, relative to 100 parts by weight of component A. If the content is less than 3.0 parts by weight, the effect of improving the wear resistance and dynamic friction coefficient is insufficient, while if the content exceeds 15.0 parts by weight, surface peeling and marbled appearance defects are observed, and the surface peeling becomes the starting point for easy scraping, resulting in a deterioration in wear resistance.

[0104] (Other additives) The resin composition of the present invention may also contain the additives described below depending on the intended use.

[0105] (i) Flame retardants The polycarbonate resin composition of the present invention may contain various compounds known as flame retardants. The incorporation of compounds used as flame retardants not only improves flame retardancy, but also improves, for example, antistatic properties, fluidity, rigidity, and thermal stability, depending on the properties of each compound.

[0106] Examples of such flame retardants include (a) organometallic salt-based flame retardants (e.g., organic alkali (earth) metal sulfonates, metal borate-based flame retardants, and metal stannate-based flame retardants), (b) organophosphorus-based flame retardants (e.g., phosphonitrile oligomer compounds, phosphonic acid amide compounds, and the like), (c) silicone-based flame retardants made of silicone compounds, and (d) halogen-based flame retardants (e.g., brominated epoxy resins, brominated polystyrene, brominated polycarbonates (including oligomers), brominated polyacrylates, and chlorinated polyethylenes, and the like).

[0107] (ii) Flame retardant synergist The polycarbonate resin composition of the present invention may further contain a flame retardant auxiliary (e.g., sodium antimonate, antimony trioxide, etc.) or an antidripping agent (e.g., polytetrafluoroethylene having fibril forming ability) and the like, which may be used in combination with the flame retardant. Polytetrafluoroethylene (PTFE) having fibril-forming ability has an extremely high molecular weight, and shows a tendency to bond PTFE to each other and become fibrous by external action such as shear force. Its molecular weight is 1 million to 10 million, more preferably 2 million to 9 million, in terms of number average molecular weight calculated from standard specific gravity. Such PTFE can be used in the form of a solid or an aqueous dispersion. In addition, such PTFE having fibril-forming ability can be used as a PTFE mixture mixed with other resins to improve dispersibility in resins and obtain better flame retardancy and mechanical properties. Examples of commercially available products of such PTFE having fibril-forming ability include Teflon (registered trademark) 6J from Mitsui DuPont Fluorochemical Co., Ltd., and Polyflon MPA FA500 and F-201L from Daikin Chemical Industries, Ltd. Representative examples of commercially available aqueous dispersions of PTFE include Fluon AD-1 and AD-936 manufactured by Asahi ICI Fluoropolymers Co., Ltd., Fluon D-1 and D-2 manufactured by Daikin Industries, Ltd., and Teflon (registered trademark) 30J manufactured by DuPont-Mitsui Fluorochemicals Co., Ltd.

[0108] Examples of the mixed form of PTFE include: (1) a method of mixing an aqueous dispersion of PTFE with an aqueous dispersion or solution of an organic polymer and co-precipitating to obtain a co-aggregated mixture (methods described in JP-A-60-258263, JP-A-63-154744, etc.); (2) a method of mixing an aqueous dispersion of PTFE with dried organic polymer particles (method described in JP-A-4-272957); (3) a method of uniformly mixing an aqueous dispersion of PTFE with a solution of organic polymer particles and simultaneously removing the respective media from the mixture (methods described in JP-A-06-220210, JP-A-08-188653, etc.); and (4) a method of polymerizing a monomer that forms an organic polymer in an aqueous dispersion of PTFE (methods described in JP-A-9-95583). (5) a method in which an aqueous dispersion of PTFE and an organic polymer dispersion are uniformly mixed, and then a vinyl monomer is polymerized in the mixed dispersion to obtain a mixture (method described in JP-A-11-29679, etc.) can be used. Commercially available products of these mixed forms of PTFE include "Metablen A3000" (trade name) manufactured by Mitsubishi Rayon Co., Ltd., and "BLENDEX B449" (trade name) manufactured by GE Specialty Chemicals.

[0109] The proportion of PTFE in the mixed form is preferably 1 to 60% by weight, more preferably 5 to 55% by weight, in 100% by weight of the PTFE mixture. When the proportion of PTFE is within this range, good dispersibility of PTFE can be achieved.

[0110] The content of this component is preferably 0.01 to 1 part by weight, more preferably 0.03 to 0.8 parts by weight, and even more preferably 0.05 to 0.6 parts by weight, per 100 parts by weight of component A. If the content is less than 0.01 part by weight, it may be difficult to obtain a flame retardant effect, and if it exceeds 1 part by weight, the appearance of the molded article may deteriorate.

[0111] (iii) Phosphorus-based stabilizers Examples of phosphorus-based stabilizers include phosphorous acid, phosphoric acid, phosphonous acid, phosphonic acid and their esters, and tertiary phosphines.

[0112] Specific examples of the phosphite compound include triphenyl phosphite, tris(nonylphenyl)phosphite, tridecyl phosphite, trioctyl phosphite, trioctadecyl phosphite, didecyl monophenyl phosphite, dioctyl monophenyl phosphite, diisopropyl monophenyl phosphite, monobutyl diphenyl phosphite, monodecyl diphenyl phosphite, monooctyl diphenyl phosphite, tris(diethylphenyl)phosphite, tris(di-iso-propylphenyl)phosphite, tris(di-n-butylphenyl)phosphite, tris(2,4-di-tert-butylphenyl)phosphite, tris(2,6-di-tert-butylphenyl)phosphite, butylphenyl)phosphite, distearyl pentaerythritol diphosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-ethylphenyl)pentaerythritol diphosphite, bis{2,4-bis(1-methyl-1-phenylethyl)phenyl}pentaerythritol diphosphite, phenyl bisphenol A pentaerythritol diphosphite, bis(nonylphenyl)pentaerythritol diphosphite, and dicyclohexyl pentaerythritol diphosphite.

[0113] Other phosphite compounds that react with dihydric phenols to form a cyclic structure can also be used, such as 2,2'-methylenebis(4,6-di-tert-butylphenyl)(2,4-di-tert-butylphenyl)phosphite, 2,2'-methylenebis(4,6-di-tert-butylphenyl)(2-tert-butyl-4-methylphenyl)phosphite, and 2,2-methylenebis(4,6-di-tert-butylphenyl)octylphosphite.

[0114] Examples of the phosphate compound include tributyl phosphate, trimethyl phosphate, tricresyl phosphate, triphenyl phosphate, trichlorophenyl phosphate, triethyl phosphate, diphenyl cresyl phosphate, diphenyl monoorthoxenyl phosphate, tributoxyethyl phosphate, dibutyl phosphate, dioctyl phosphate, diisopropyl phosphate, and the like, and preferably triphenyl phosphate and trimethyl phosphate.

[0115] Examples of the phosphonite compounds include tetrakis(2,4-di-tert-butylphenyl)-4,4'-biphenylene diphosphonite, tetrakis(2,4-di-tert-butylphenyl)-4,3'-biphenylene diphosphonite, tetrakis(2,4-di-tert-butylphenyl)-3,3'-biphenylene diphosphonite, tetrakis(2,6-di-tert-butylphenyl)-4,4'-biphenylene diphosphonite, tetrakis(2,6-di-tert-butylphenyl)-4,3'-biphenylene diphosphonite, tetrakis(2,6-di-tert-butylphenyl)-3,3'-biphenylene diphosphonite, bis(2,4-di-tert-butylphenyl)-4-phenyl-phenylphosphonite, bis Examples of the phosphonite include (2,4-di-tert-butylphenyl)-3-phenyl-phenylphosphonite, bis(2,6-di-n-butylphenyl)-3-phenyl-phenylphosphonite, bis(2,6-di-tert-butylphenyl)-4-phenyl-phenylphosphonite, and bis(2,6-di-tert-butylphenyl)-3-phenyl-phenylphosphonite. Tetrakis(di-tert-butylphenyl)-biphenylene diphosphonite and bis(di-tert-butylphenyl)-phenyl-phenylphosphonite are preferred, and tetrakis(2,4-di-tert-butylphenyl)-biphenylene diphosphonite and bis(2,4-di-tert-butylphenyl)-phenyl-phenylphosphonite are more preferred. Such phosphonite compounds can be used in combination with the phosphite compounds having an aryl group substituted with two or more alkyl groups, and are therefore preferred.

[0116] Examples of the phosphonate compound include dimethyl benzenephosphonate, diethyl benzenephosphonate, and dipropyl benzenephosphonate.

[0117] Examples of tertiary phosphines include triethylphosphine, tripropylphosphine, tributylphosphine, trioctylphosphine, triamylphosphine, dimethylphenylphosphine, dibutylphenylphosphine, diphenylmethylphosphine, diphenyloctylphosphine, triphenylphosphine, tri-p-tolylphosphine, trinaphthylphosphine, and diphenylbenzylphosphine. A particularly preferred tertiary phosphine is triphenylphosphine.

[0118] The phosphorus-based stabilizers may be used alone or in combination of two or more. Among the phosphorus-based stabilizers, phosphonite compounds or phosphite compounds represented by the following general formula [7] are preferred.

[0119] [ka]

[0120] (In the above general formula [7], R and R' represent an alkyl group having 6 to 30 carbon atoms or an aryl group having 6 to 30 carbon atoms, and may be the same or different.)

[0121] As described above, the phosphonite compound is preferably tetrakis(2,4-di-tert-butylphenyl)-biphenylene diphosphonite, and stabilizers containing this phosphonite as a main component are commercially available as Sandostab P-EPQ (trademark, manufactured by Clariant) and Irgafos P-EPQ (trademark, manufactured by CIBA SPECIALTY CHEMICALS), either of which can be used.

[0122] Among the above formula [7], more suitable phosphite compounds are distearyl pentaerythritol diphosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite, and bis{2,4-bis(1-methyl-1-phenylethyl)phenyl}pentaerythritol diphosphite.

[0123] Distearyl pentaerythritol diphosphite is commercially available as ADK STAB PEP-8 (trademark, manufactured by Asahi Denka Kogyo Co., Ltd.) and JPP681S (trademark, manufactured by Johoku Chemical Industry Co., Ltd.), and any of these can be used. Bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite is commercially available as ADK STAB PEP-24G (trademark, manufactured by Asahi Denka Kogyo Co., Ltd.), Alkanox P-24 (trademark, manufactured by Great Lakes), Ultranox P626 (trademark, manufactured by GE Specialty Chemicals), Doverphos S-9432 (trademark, manufactured by Dover Chemical), and Irgaofos 126 and 126FF (trademarks, manufactured by CIBA SPECIALTY CHEMICALS), and any of these can be used. Bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite is commercially available as ADK STAB PEP-36 (trademark, manufactured by Asahi Denka Kogyo Co., Ltd.) and can be easily used. Bis{2,4-bis(1-methyl-1-phenylethyl)phenyl}pentaerythritol diphosphite is commercially available as ADK STAB PEP-45 (trademark, manufactured by Asahi Denka Kogyo Co., Ltd.) and Doverphos S-9228 (trademark, manufactured by Dover Chemical Co., Ltd.), and either can be used.

[0124] (iv) Hindered phenol antioxidants As the hindered phenol compound, various compounds that are usually blended in resins can be used. Examples of such hindered phenol compounds include α-tocopherol, butyl hydroxytoluene, sinapyl alcohol, vitamin E, octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 2-tert-butyl-6-(3'-tert-butyl-5'-methyl-2'-hydroxybenzyl)-4-methylphenyl acrylate, 2,6-di-tert-butyl-4-(N,N-dimethylaminomethyl)phenol, 3,5-di-tert-butyl-4-hydroxybenzyl Phosphonate diethyl ester, 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 2,2'-methylenebis(4-ethyl-6-tert-butylphenol), 4,4'-methylenebis(2,6-di-tert-butylphenol), 2,2'-methylenebis(4-methyl-6-cyclohexylphenol), 2,2'-dimethylene-bis(6-α-methyl-benzyl-p-cresol), 2,2'-ethylidene-bis(4,6-di-tert-butylphenol), 2,2'-butylidene-bis(4 -methyl-6-tert-butylphenol), 4,4'-butylidenebis(3-methyl-6-tert-butylphenol), triethylene glycol-N-bis-3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate, 1,6-hexanediol bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], bis[2-tert-butyl-4-methyl-6-(3-tert-butyl-5-methyl-2-hydroxybenzyl)phenyl]terephthalate, 3,9- Bis{2-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]-1,1,-dimethylethyl}-2,4,8,10-tetraoxaspiro[5,5]undecane, 4,4'-thiobis(6-tert-butyl-m-cresol), 4,4'-thiobis(3-methyl-6-tert-butylphenol), 2,2'-thiobis(4-methyl-6-tert-butylphenol), bis(3,5-di-tert-butyl-4-hydroxybenzyl)sulfide, 4,4'-dithiobis(2,6-di-tert-butylphenol), 4,4'-tri-thiobis(2,6-di-tert-butylphenol), 2,2-thiodiethylene bis-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 2,4-bis(n-octylthio)-6-(4-hydroxy-3,5-di-tert-butylanilino)-1,3,5-triazine, N,N'-hexamethylene bis-(3,5-di-tert-butyl-4-hydroxyhydrocinnamide), N,N'-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, tris(3,5-di-tert-butyl-4-hydroxyphenyl)isocyanurate, tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanurate, 1,3,5-tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl)isocyanurate 1,3,5-tris-2[3(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxy]ethyl isocyanurate, tetrakis[methylene-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]methane, triethylene glycol-N-bis-3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate, triethylene glycol-N-bis-3-(3-tert-butyl-4-hydroxy-5-methylphenyl)acetate, 3,9-bis[2-{3- (3-tert-butyl-4-hydroxy-5-methylphenyl)acetyloxy}-1,1-dimethylethyl]-2,4,8,10-tetraoxaspiro[5,5]undecane, tetrakis[methylene-3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate]methane, 1,3,5-trimethyl-2,4,6-tris(3-tert-butyl-4-hydroxy-5-methylbenzyl)benzene, and tris(3-tert-butyl-4-hydroxy-5-methylbenzyl)isocyanurate are examples.

[0125] Among the above compounds, tetrakis[methylene-3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate]methane, octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and 3,9-bis[2-{3-(3-t-butyl-4-hydroxy-5-methylphenyl)propionyloxy}-1,1-dimethylethyl]-2,4,8,10-tetraoxaspiro[5,5]undecane are preferably used in the present invention. In particular, 3,9-bis[2-{3-(3-t-butyl-4-hydroxy-5-methylphenyl)propionyloxy}-1,1-dimethylethyl]-2,4,8,10-tetraoxaspiro[5,5]undecane is preferred. The above hindered phenol-based antioxidants can be used alone or in combination of two or more.

[0126] It is preferable that either the phosphorus-based stabilizer or the hindered phenol-based antioxidant is contained, and it is more preferable that they are used in combination. The content of the phosphorus-based stabilizer and the hindered phenol-based antioxidant is preferably 0.001 to 3 parts by weight, more preferably 0.005 to 2 parts by weight, and even more preferably 0.01 to 1 part by weight, per 100 parts by weight of the A component. In the case of a combination, it is more preferable that 0.01 to 0.3 parts by weight of the phosphorus-based stabilizer and 0.01 to 0.3 parts by weight of the hindered phenol-based antioxidant are contained per 100 parts by weight of the A component.

[0127] (v) Other heat stabilizers The resin composition of the present invention may contain other heat stabilizers in addition to the phosphorus-based stabilizer and hindered phenol-based antioxidant. Such other heat stabilizers are preferably used in combination with either one of these stabilizers and antioxidants, and are particularly preferably used in combination with both. As such other heat stabilizers, lactone-based stabilizers such as the reaction product of 3-hydroxy-5,7-di-tert-butyl-furan-2-one and o-xylene (details of such stabilizers are described in JP-A-7-233160) are preferred. Examples of such a compound include Irganox HP-136 (trademark, manufactured by CIBA SPECIALTY CHEMICALS), which is commercially available and can be used. Furthermore, stabilizers obtained by mixing such a compound with various phosphite compounds and hindered phenol compounds are commercially available. For example, Irganox HP-2921 manufactured by the above company is a suitable example. In the present invention, such premixed stabilizers can also be used. The amount of lactone-based stabilizer to be blended is preferably 0.0005 to 0.05 parts by weight, more preferably 0.001 to 0.03 parts by weight, based on 100 parts by weight of component A.

[0128] Other examples of the stabilizer include sulfur-containing stabilizers such as pentaerythritol tetrakis (3-mercaptopropionate), pentaerythritol tetrakis (3-laurylthiopropionate), and glycerol-3-stearylthiopropionate. Such stabilizers are particularly effective when the resin composition is applied to rotational molding. The content of such sulfur-containing stabilizers is preferably 0.001 to 0.1 parts by weight, more preferably 0.01 to 0.08 parts by weight, based on 100 parts by weight of component A.

[0129] (vi) Mold release agent The polycarbonate resin composition of the present invention preferably further contains a mold release agent for the purpose of improving the productivity during molding and reducing distortion of the molded product. As such a mold release agent, a known one can be used. For example, saturated fatty acid esters, unsaturated fatty acid esters, polyolefin waxes (polyethylene wax, 1-alkene polymers, etc., those modified with functional group-containing compounds such as acid modification can also be used), silicone compounds, fluorine compounds (fluorine oils represented by polyfluoroalkyl ethers, etc.), paraffin wax, beeswax, etc. can be mentioned. Among them, fatty acid esters can be mentioned as a preferred mold release agent. Such fatty acid esters are esters of aliphatic alcohols and aliphatic carboxylic acids. Such aliphatic alcohols may be monohydric alcohols or polyhydric alcohols having dihydric or higher valences. The carbon number of the alcohol is in the range of 3 to 32, more preferably in the range of 5 to 30. Examples of such monohydric alcohols include dodecanol, tetradecanol, hexadecanol, octadecanol, eicosanol, tetracosanol, ceryl alcohol, and triacontanol. Examples of such polyhydric alcohols include pentaerythritol, dipentaerythritol, tripentaerythritol, polyglycerol (triglycerol to hexaglycerol), ditrimethylolpropane, xylitol, sorbitol, and mannitol. In the fatty acid ester of the present invention, polyhydric alcohols are more preferred.

[0130] On the other hand, the aliphatic carboxylic acid preferably has 3 to 32 carbon atoms, and particularly preferably has 10 to 22 carbon atoms. Examples of the aliphatic carboxylic acid include saturated aliphatic carboxylic acids such as decanoic acid, undecanoic acid, dodecanoic acid, tridecanoic acid, tetradecanoic acid, pentadecanoic acid, hexadecanoic acid (palmitic acid), heptadecanoic acid, octadecanoic acid (stearic acid), nonadecanoic acid, behenic acid, icosanoic acid, and docosanoic acid, and unsaturated aliphatic carboxylic acids such as palmitoleic acid, oleic acid, linoleic acid, linolenic acid, eicosenoic acid, eicosapentaenoic acid, and cetoleic acid. Among the above, the aliphatic carboxylic acid is preferably one having 14 to 20 carbon atoms. Among them, saturated aliphatic carboxylic acids are preferred. Stearic acid and palmitic acid are particularly preferred.

[0131] The above-mentioned aliphatic carboxylic acids such as stearic acid and palmitic acid are usually produced from natural oils and fats such as animal oils and fats such as beef tallow and lard, and vegetable oils and fats such as palm oil and sunflower oil, and therefore these aliphatic carboxylic acids are usually mixtures containing other carboxylic acid components with different numbers of carbon atoms. Therefore, in the production of the fatty acid ester of the present invention, aliphatic carboxylic acids produced from such natural oils and fats and in the form of a mixture containing other carboxylic acid components, particularly stearic acid and palmitic acid, are preferably used.

[0132] The fatty acid ester of the present invention may be either a partial ester or a full ester (full ester). However, partial esters usually have a high hydroxyl value and tend to induce decomposition of the resin at high temperatures, so full esters are more preferred. The acid value of the fatty acid ester of the present invention is preferably 20 or less, more preferably in the range of 4 to 20, and even more preferably in the range of 4 to 12, from the viewpoint of thermal stability. The acid value can be substantially 0. The hydroxyl value of the fatty acid ester is more preferably in the range of 0.1 to 30. The iodine value is preferably 10 or less. The iodine value can be substantially 0. These properties can be determined by the method specified in JIS K 0070.

[0133] The content of the mold release agent is preferably 0.005 to 2 parts by weight, more preferably 0.01 to 1 part by weight, and even more preferably 0.05 to 0.5 parts by weight, based on 100 parts by weight of the A component. In this range, the polycarbonate resin composition may have good mold releasability and roll releasability. In particular, such an amount of fatty acid ester provides a flame-retardant resin composition having good mold releasability and roll releasability without impairing good hue.

[0134] (vii) Ultraviolet absorbers The polycarbonate resin composition of the present invention preferably contains an ultraviolet absorbing agent to suppress ultraviolet degradation in outdoor applications.Specific examples of the ultraviolet absorbing agent include benzophenone-based agents such as 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-octoxybenzophenone, 2-hydroxy-4-benzyloxybenzophenone, 2-hydroxy-4-methoxy-5-sulfoxybenzophenone, 2,2'-dihydroxy-4-methoxybenzophenone, 2,2',4,4'-tetrahydroxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxy-5-sodiumsulfoxybenzophenone, bis(5-benzoyl-4-hydroxy-2-methoxyphenyl)methane, 2-hydroxy-4-n-dodecyloxybenzophenone, and 2-hydroxy-4-methoxy-2'-carboxybenzophenone.Specific examples of the ultraviolet absorber include benzotriazole-based ultraviolet absorbers such as 2-(2-hydroxy-5-methylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, 2-(2-hydroxy-3,5-dicumylphenyl)phenylbenzotriazole, 2-(2-hydroxy-3-tert-butyl-5-methylphenyl)-5-chlorobenzotriazole, 2,2'-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol], 2-(2-hydroxy-3,5-di-tert-butylphenyl)benzotriazole, 2-(2-hydroxy-3,5-di-tert-butylphenyl)-5-chlorobenzotriazole, 2-(2-hydroxy-3,5-di-tert-amylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, Examples of the copolymer include 2-hydroxyphenyl-2H-benzotriazole skeleton such as 2-(2-hydroxy-5-acryloxyethylphenyl)-2H-benzotriazole, 2-(2-hydroxy-5-tert-butylphenyl)-benzotriazole, 2-(2-hydroxy-4-octoxyphenyl)-benzotriazole, 2,2'-methylenebis(4-cumyl-6-benzotriazolephenyl), 2,2'-p-phenylenebis(1,3-benzoxazin-4-one), and 2-[2-hydroxy-3-(3,4,5,6-tetrahydrophthalimidomethyl)-5-methylphenyl]benzotriazole, and copolymers of 2-(2'-hydroxy-5-methacryloxyethylphenyl)-2H-benzotriazole and vinyl monomers copolymerizable with the monomer, and copolymers of 2-(2'-hydroxy-5-acryloxyethylphenyl)-2H-benzotriazole and vinyl monomers copolymerizable with the monomer.Specific examples of the ultraviolet absorber include, in the hydroxyphenyltriazine series, 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-hexyloxyphenol, 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-methyloxyphenol, 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-ethyloxyphenol, 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-propyloxyphenol, and 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-butyloxyphenol.Further examples include compounds in which the phenyl group of the above-mentioned compounds is a 2,4-dimethylphenyl group, such as 2-(4,6-bis(2,4-dimethylphenyl)-1,3,5-triazin-2-yl)-5-hexyloxyphenol. Specific examples of the ultraviolet absorbent include cyclic iminoesters such as 2,2'-p-phenylenebis(3,1-benzoxazine-4-one), 2,2'-m-phenylenebis(3,1-benzoxazine-4-one), and 2,2'-p,p'-diphenylenebis(3,1-benzoxazine-4-one). Specific examples of the ultraviolet absorbent include cyanoacrylates such as 1,3-bis-[(2'-cyano-3',3'-diphenylacryloyl)oxy]-2,2-bis[(2-cyano-3,3-diphenylacryloyl)oxy]methyl)propane and 1,3-bis-[(2-cyano-3,3-diphenylacryloyl)oxy]benzene. Furthermore, the ultraviolet absorber may be a polymer type ultraviolet absorber obtained by copolymerizing such an ultraviolet absorbing monomer and / or a light stable monomer with a monomer such as an alkyl (meth)acrylate by adopting a structure of a radically polymerizable monomer compound. Suitable examples of the ultraviolet absorbing monomer include compounds containing a benzotriazole skeleton, a benzophenone skeleton, a triazine skeleton, a cyclic imino ester skeleton, and a cyanoacrylate skeleton in the ester substituent of a (meth)acrylic acid ester.Among the above, benzotriazole and hydroxyphenyltriazine are preferred in terms of ultraviolet absorbing ability, and cyclic iminoester and cyanoacrylate are preferred in terms of heat resistance and color. Specific examples include "Chemisorb 79" from Chemipro Chemical Co., Ltd. and "Tinuvin 234" from BASF Japan Ltd. The ultraviolet absorbing agents may be used alone or in a mixture of two or more kinds.

[0135] The content of the ultraviolet absorber is preferably 0.01 to 3 parts by weight, more preferably 0.01 to 1 part by weight, further preferably 0.05 to 1 part by weight, and particularly preferably 0.05 to 0.5 parts by weight, relative to 100 parts by weight of component A. If the content is less than 0.01 part by weight, the weather resistance may be insufficient, and if it exceeds 3 parts by weight, the flame retardancy may be insufficient.

[0136] (viii) Dyes and pigments The polycarbonate resin composition of the present invention further contains various dyes and pigments, and can provide molded products that exhibit a variety of designs. Examples of dyes and pigments used in the present invention include perylene dyes, coumarin dyes, thioindigo dyes, anthraquinone dyes, thioxanthone dyes, ferrocyanides such as Prussian blue, perinone dyes, quinoline dyes, quinacridone dyes, dioxazine dyes, isoindolinone dyes, and phthalocyanine dyes. Furthermore, the polycarbonate resin composition of the present invention can be blended with a metallic pigment to obtain a better metallic color. Aluminum powder is suitable as the metallic pigment. In addition, by blending a fluorescent brightener or other fluorescent dye that emits light, a better design effect that makes use of the luminous color can be imparted.

[0137] (ix) Fluorescent whitening agents In the resin composition of the present invention, the fluorescent brightener is not particularly limited as long as it is used to improve the color tone of the resin or the like to white or bluish white, and examples thereof include stilbene-based, benzimidazole-based, benzoxazole-based, naphthalimide-based, rhodamine-based, coumarin-based, and oxazine-based compounds. Specific examples include CI Fluorescent Brightener 219:1, Eastman Chemical Company's EASTOBRITE OB-1, and Showa Chemical Company's "HAKKOL PSR." Here, the fluorescent The optical brightening agent has the effect of absorbing the ultraviolet energy of light and radiating this energy in the visible region. The content of the optical brightening agent is preferably 0.001 to 0.1 parts by weight, more preferably 0.001 to 0.05 parts by weight, based on 100 parts by weight of component A. Even if the content exceeds 0.1 parts by weight, the effect of improving the color tone of the composition may be small.

[0138] (x) Compounds capable of absorbing heat rays The polycarbonate resin composition of the present invention may contain a compound having heat absorbing ability. Suitable examples of such compounds include phthalocyanine-based near infrared absorbing agents, metal oxide-based near infrared absorbing agents such as ATO, ITO, iridium oxide, ruthenium oxide, immonium oxide, and titanium oxide, various metal compounds having excellent near infrared absorbing ability such as metal boride-based and tungsten oxide-based near infrared absorbing agents such as lanthanum boride, cerium boride, and tungsten boride, and carbon fillers. As such phthalocyanine-based near infrared absorbing agents, for example, MIR-362 manufactured by Mitsui Chemicals, Inc. is commercially available and easily available. Examples of carbon fillers include carbon black, graphite (both natural and artificial), and fullerene, and preferably carbon black and graphite. These can be used alone or in combination of two or more. The content of the phthalocyanine-based near infrared absorber is preferably 0.0005 to 0.2 parts by weight, more preferably 0.0008 to 0.1 parts by weight, and even more preferably 0.001 to 0.07 parts by weight, relative to 100 parts by weight of component A. The contents of the metal oxide-based near infrared absorber, metal boride-based near infrared absorber, and carbon filler are preferably in the range of 0.1 to 200 ppm (weight ratio), and more preferably in the range of 0.5 to 100 ppm, in the polycarbonate resin composition of the present invention.

[0139] (xi) Light diffusing agent The polycarbonate resin composition of the present invention can contain a light diffusing agent to impart a light diffusing effect. Examples of such light diffusing agents include polymer fine particles, inorganic fine particles with a low refractive index such as calcium carbonate, and composites thereof. Such polymer fine particles are fine particles already known as light diffusing agents for polycarbonate resins. More preferred examples include acrylic crosslinked particles with a particle size of several μm and silicone crosslinked particles represented by polyorganosilsesquioxane. Examples of the shape of the light diffusing agent include spherical, discoid, columnar, and amorphous shapes. Such a sphere does not need to be a perfect sphere and includes deformed ones, and such a columnar shape includes a cube. A preferred light diffusing agent is spherical, and the more uniform the particle size, the more preferred it is. The content of the light diffusing agent is preferably 0.005 to 20 parts by weight, more preferably 0.01 to 10 parts by weight, and even more preferably 0.01 to 3 parts by weight, relative to 100 parts by weight of component A. Two or more types of light diffusing agents can be used in combination.

[0140] (xii) Highly light-reflecting white pigments The polycarbonate resin composition of the present invention can contain a highly light-reflective white pigment to impart a light-reflecting effect. Titanium dioxide (particularly titanium dioxide treated with an organic surface treatment agent such as silicone) pigment is particularly preferred as such a white pigment. The content of such highly light-reflective white pigment is preferably 3 to 30 parts by weight, more preferably 8 to 25 parts by weight, per 100 parts by weight of component A. Two or more types of highly light-reflective white pigments can be used in combination.

[0141] (xiii) Antistatic agents The polycarbonate resin composition of the present invention may be required to have antistatic properties, and in such cases, it is preferable to include an antistatic agent. Examples of such antistatic agents include (1) arylsulfonic acid phosphonium salts, such as dodecylbenzenesulfonic acid phosphonium salts, and organic sulfonic acid phosphonium salts, such as alkylsulfonic acid phosphonium salts, and boric acid phosphonium salts, such as tetrafluoroborate phosphonium salts. The content of the phosphonium salt is appropriately 5 parts by weight or less, preferably 0.05 to 5 parts by weight, more preferably 1 to 3.5 parts by weight, and even more preferably 1. The range is 5 to 3 parts by weight. Examples of the antistatic agent include (2) organic sulfonate alkali (earth) metal salts such as lithium organic sulfonate, sodium organic sulfonate, potassium organic sulfonate, cesium organic sulfonate, rubidium organic sulfonate, calcium organic sulfonate, magnesium organic sulfonate, and barium organic sulfonate. As described above, such metal salts are also used as flame retardants. More specifically, such metal salts include metal salts of dodecylbenzenesulfonic acid and metal salts of perfluoroalkanesulfonic acid. The content of the organic sulfonate alkali (earth) metal salt is suitably 0.5 parts by weight or less, preferably 0.001 to 0.3 parts by weight, and more preferably 0.005 to 0.2 parts by weight, relative to 100 parts by weight of component A. In particular, alkali metal salts such as potassium, cesium, and rubidium are suitable.

[0142] Examples of the antistatic agent include (3) organic ammonium sulfonates such as ammonium alkylsulfonates and ammonium arylsulfonates. The amount of the ammonium salt is preferably 0.05 parts by weight or less based on 100 parts by weight of the resin component. Examples of the antistatic agent include (4) polymers containing a poly(oxyalkylene) glycol component as a constituent component, such as polyether ester amide. The amount of the polymer is preferably 5 parts by weight or less based on 100 parts by weight of the resin component.

[0143] (xiv) Filling material The polycarbonate resin composition of the present invention can contain various fillers known as reinforcing fillers. As such fillers, various fibrous fillers, plate-like fillers, and granular fillers can be used. Here, the fibrous filler is a filler having a fibrous shape (including rod-like, needle-like, or a shape in which the axis extends in multiple directions), and the plate-like filler is a filler having a plate-like shape (including a filler having an uneven surface or a filler having a curved plate). The granular filler is a filler having a shape other than these, including an indefinite shape. The above-mentioned fibrous or plate-like shapes are often clear from observation of the shape of the filler, but for example, as a difference from the so-called indefinite shape, a filler having an aspect ratio of 3 or more can be said to be fibrous or plate-like.

[0144] Preferred examples of the plate-like filler include glass flakes, talc, mica, kaolin, metal flakes, carbon flakes, and graphite, as well as plate-like fillers obtained by surface-coating these fillers with different materials such as metals and metal oxides. The particle size is preferably in the range of 0.1 to 300 μm. The particle size refers to the value of the median diameter (D50) of the particle size distribution measured by the X-ray transmission method, which is one of the liquid phase precipitation methods, in the region up to about 10 μm, the value of the median diameter (D50) of the particle size distribution measured by the laser diffraction / scattering method in the region of 10 to 50 μm, and the value of the vibration sieving method in the region of 50 to 300 μm. The particle size is the particle size in the resin composition. The plate-like filler may be surface-treated with various coupling agents such as silane-, titanate-, aluminate-, and zirconate-based coupling agents, or may be in the form of granules that have been bundled or compressed with various resins such as olefin-, styrene-, acrylic-, polyester-, epoxy-, and urethane-based resins, or higher fatty acid esters.

[0145] The fiber diameter of the fibrous filler is preferably in the range of 0.1 to 20 μm. The upper limit of the fiber diameter is more preferably 13 μm, and even more preferably 10 μm. Meanwhile, the lower limit of the fiber diameter is preferably 1 μm. The fiber diameter here refers to the number average fiber diameter. The number average fiber diameter is a value calculated from an image obtained by observing, with a scanning electron microscope, the residue collected after dissolving the molded product in a solvent or decomposing the resin with a basic compound, and the ashing residue collected after ashing in a crucible. Examples of such fibrous fillers include glass fibers, flat cross-section glass fibers, milled glass fibers, carbon fibers, milled carbon fibers, metal fibers, asbestos, rock wool, ceramic fibers, slag fibers, potassium titanate whiskers, boron whiskers, aluminum borate whiskers, calcium carbonate whiskers, titanium oxide whiskers, wollastonite, xonotlite, palygorskite (attapulgite), and sepiolite, and other fibrous inorganic fillers, typified by heat-resistant organic fibers such as aramid fibers, polyimide fibers, and polybenzothiazole fibers, as well as fibrous fillers in which the surface of these fillers is coated with a different material such as a metal or metal oxide. Examples of fillers in which a different material is coated on the surface include metal-coated glass fibers, metal-coated glass flakes, titanium oxide-coated glass flakes, and metal-coated carbon fibers. The method of surface coating of different materials is not particularly limited, and examples thereof include various known plating methods (e.g., electrolytic plating, electroless plating, hot-dip plating, etc.), vacuum deposition, ion plating, CVD (e.g., thermal CVD, MOCVD, plasma CVD, etc.), PVD, and sputtering. Here, the fibrous filler refers to a fibrous filler having an aspect ratio of 3 or more, preferably 5 or more, and more preferably 10 or more. The upper limit of the aspect ratio is about 10,000, and preferably 200. The aspect ratio of such a filler is the value in the resin composition.The flat cross-section glass fiber is a glass fiber having an average major axis of 10 to 50 μm, preferably 15 to 40 μm, more preferably 20 to 35 μm, and an average major axis to minor axis ratio (major axis / minor axis) of 1.5 to 8, preferably 2 to 6, and even more preferably 2.5 to 5. The fibrous filler may be surface-treated with various coupling agents, bundled with various resins, and granulated by compression, in the same manner as the plate-like filler. The content of such a filler is preferably 200 parts by weight or less, more preferably 100 parts by weight or less, even more preferably 50 parts by weight or less, and particularly preferably 30 parts by weight or less, relative to 100 parts by weight of component A.

[0146] (xv) Other resins and elastomers In the polycarbonate resin composition of the present invention, other resins or elastomers may be used in small proportions in place of a part of the resin component of component A, as long as the effects of the present invention are exhibited. The amount of the other resins or elastomers is preferably 20% by weight or less, more preferably 10% by weight or less, and even more preferably 5% by weight or less, based on 100% by weight of the total with component A. Examples of such other resins include polyester resins such as polyethylene terephthalate and polybutylene terephthalate, polyamide resins, polyimide resins, polyetherimide resins, polyurethane resins, silicone resins, polyphenylene ether resins, polyphenylene sulfide resins, polysulfone resins, polymethacrylate resins, phenolic resins, and epoxy resins. Examples of elastomers include isobutylene / isoprene rubber, styrene / butadiene rubber, ethylene / propylene rubber, acrylic elastomers, polyester elastomers, polyamide elastomers, and core-shell elastomers such as MBS (methyl methacrylate / styrene / butadiene) rubber, MB (methyl methacrylate / butadiene) rubber, and MAS (methyl methacrylate / acrylonitrile / styrene) rubber.

[0147] (xvi) Other additives The polycarbonate resin composition of the present invention may contain other flow modifiers, antibacterial agents, dispersants such as liquid paraffin, photocatalytic antifouling agents, photochromic agents, and the like.

[0148] <Production of Resin Composition> Any method may be used to produce the resin composition of the present invention. For example, the A component, the B component, and any other components may be thoroughly mixed using a premixing means such as a V-type blender, a Henschel mixer, a mechanochemical device, or an extrusion mixer, and then granulated as necessary using an extrusion granulator or a briquetting machine, followed by melt kneading using a melt kneader such as a vented twin-screw extruder, and pelletizing using a device such as a pelletizer.

[0149] <Production of molded products> The resin composition of the present invention can be obtained by injection molding such pellets. In such injection molding, not only the usual cold runner type molding method but also hot runners that enable runnerless production can be used. In addition to the usual molding method, gas-assisted injection molding, injection compression molding, ultra-high speed injection molding, injection press molding, two-color molding, sandwich molding, in-mold coating molding, insert molding, foam molding (including those using supercritical fluids), rapid heating and cooling mold molding, heat insulating mold molding, and in-mold remelting molding, as well as molding methods consisting of combinations thereof, can be used for injection molding. Furthermore, various surface treatments can be performed on molded articles formed from the resin composition. Examples of surface treatments include decorative painting, hard coating, water-repellent and oil-repellent coating, hydrophilic coating, ultraviolet absorbing coating, infrared absorbing coating, electromagnetic wave absorbing coating, heat generating coating, antistatic coating, antistatic coating, conductive coating, and metallizing (plating, chemical vapor deposition (CVD), physical vapor deposition (PVD), thermal spraying, etc.). EXAMPLES

[0150] The present invention will be described in more detail below with reference to examples, but these are not intended to limit the present invention. Unless otherwise specified, parts in the examples are parts by weight and % is % by weight. Evaluations were performed according to the following methods.

[0151] (Evaluation of polycarbonate-polydiorganosiloxane copolymers) (1) Average repeat number of polydiorganosiloxane (p+q) Using NMR JNM-AL400 manufactured by JEOL Ltd., polycarbonate-polydiorganosiloxane copolymer was measured. 1 The H-NMR spectrum was measured, and the average chain length p+q was calculated by comparing the integral ratio of the peak derived from the hydroxyaryl terminal with the integral ratio of the peak derived from the polydiorganosiloxane.

[0152] (Evaluation of Resin Composition) The pellets obtained by the method described below were dried in a hot air circulation dryer at 130°C for 6 hours, and then a three-stage plate with a width of 50 mm, length of 90 mm, and thicknesses of 3 mm (length 20 mm), 2 mm (length 45 mm), and 1 mm (length 25 mm) from the gate side was molded using a mold with a cavity surface with an arithmetic mean roughness (Ra) of 0.03 μm, under conditions of a cylinder temperature of 280°C, a mold temperature of 80°C, a pressure holding time of 20 seconds, and a cooling time of 20 seconds, using an injection molding machine J-75E3 manufactured by Japan Steel Works, Ltd. This was used to evaluate the appearance, wear resistance, and dynamic friction coefficient by the following methods.

[0153] (exterior) The plate was visually observed and evaluated according to the following criteria. ⊚: No surface peeling or marbled appearance defects were observed. ◯: Surface peeling or marbled appearance defect is observed, but is minor. ×: Significant surface peeling or marbled appearance defect is observed.

[0154] (Wear resistance) Using a reciprocating friction and wear tester AFT-15M manufactured by Orientec Co., Ltd., a Φ5mm SUS ball was placed on the 2mm part of the above plate and reciprocated 1000 times under the conditions of a load of 1kg, a movement distance of 25mm, and a movement speed of 25mm / s. After the test, the wear marks remaining on the plate were visually observed and evaluated according to the following criteria. : Almost no wear marks are visible. A: There are traces of wear, but they are minor. ×: Significant wear marks are observed.

[0155] (Kinematic friction coefficient) In the above evaluation of wear resistance, the load (kg) applied to the load cell connected to the part holding the SUS ball during 1000 reciprocations was evaluated as the dynamic friction coefficient of the sample.

[0156] The following raw materials were used: (Component A-1) A-1: Polycarbonate-polydiorganosiloxane copolymer produced by the production method of Example 8 described in WO2011 / 013846 below [Manufacturing method] A reactor equipped with a thermometer, a stirrer, and a reflux condenser was charged with 21,592 parts of ion-exchanged water and 3,675 parts of 48.5% aqueous sodium hydroxide solution, and 3,880 parts (17.00 moles) of 2,2-bis(4-hydroxyphenyl)propane (bisphenol A) as the dihydric phenol (I) represented by the general formula [5] and 7.6 parts of hydrosulfite were dissolved therein. Then, 14,565 parts of methylene chloride (10 molar equivalents relative to the total amount of dihydric phenols) was added, and 1,900 parts of phosgene was blown in over a period of 60 minutes at 22-30°C with stirring. 7283 parts of methylene chloride (5 molar equivalents relative to the total amount of dihydric phenol) was added, and a solution of 1131 parts of 48.5% aqueous sodium hydroxide solution and 108 parts of p-tert-butylphenol dissolved in 800 parts of methylene chloride (0.55 molar equivalents relative to the total amount of dihydric phenol) was added, and while stirring, a solution of 430 parts (0.139 moles) of KF-2201 (p+q=40) manufactured by Shin-Etsu Chemical Co., Ltd., as a dihydric phenol (II) having a polydiorganosiloxane structure represented by the general formula [6], dissolved in 800 parts of methylene chloride (0.55 molar equivalents relative to the total amount of dihydric phenol) was added at a rate of 0.0004 molar equivalents / min relative to the dihydric phenol (I) to emulsify, and then vigorously stirred again. Under such stirring, 4.3 parts of triethylamine was added when the reaction liquid was at 26°C, and the reaction was terminated by continuing stirring at a temperature of 26-31°C for 1 hour. After the reaction was completed, the organic phase was separated, diluted with methylene chloride, washed with water, and then acidified with hydrochloric acid and washed with water. When the conductivity of the aqueous phase was almost the same as that of ion-exchanged water, it was put into a kneader filled with warm water and the methylene chloride was evaporated while stirring to obtain a polycarbonate-polydiorganosiloxane copolymer powder. After dehydration, it was dried for 12 hours at 120°C in a hot air circulation dryer. The average polydiorganosiloxane repeat number (p+q) of the obtained polycarbonate-polydiorganosiloxane copolymer was 40.

[0157] (Component A-2) A-2: Linear aromatic polycarbonate resin powder with a solution viscosity of 23,900 and a molecular weight of 23,900, which has a repeating skeleton of 2,2-bis(4-hydroxyphenyl)propane (Teijin Ltd. Panlite L-1250WP) (B component) B-1: (meth)acrylic modified polyorganosiloxane (Chaline R170 (trade name) manufactured by Nissin Chemical Industry Co., Ltd., a graft copolymer using polydimethylsiloxane as the B1 component and methyl methacrylate as the B2 component, polydimethylsiloxane content 70% by weight)

[0158] [Production of polycarbonate resin composition] The components A-1, A-2, and B were weighed and mixed uniformly according to the composition shown in Table 1, and melt-kneaded using a vented twin-screw extruder to obtain pellets. The vented twin-screw extruder used was a KTX-30 (diameter 30 mmφ) made by Kobe Steel, Ltd. Strands were extruded under conditions of cylinder temperature and die temperature of 280°C, screw speed of 150 rpm, discharge rate of 20 kg / h, and vent suction of 3 kPa, and after cooling in a water bath, the strands were cut using a pelletizer and pelletized. The results of various evaluations are shown in Table 1.

[0159] [Table 1]

[0160] As is clear from Table 1, in Examples 1 to 6, good appearance, abrasion resistance, and a low dynamic friction coefficient are all achieved. In contrast, in Comparative Example 1, which does not contain component A-1, and In Comparative Example 2, where the content of component A-2 exceeds the upper limit, component B is not compatible with component A-2, and surface peeling occurs, resulting in poor appearance. In addition, the surface peeling causes strong wear marks, resulting in poor wear resistance. In Comparative Example 3, where the content of component B is below the lower limit, the appearance is good, but the effects of improving wear resistance and reducing the dynamic friction coefficient are insufficient.

Claims

1. (A) (A-1) 1 to 100 parts by weight of a polycarbonate-polydiorganosiloxane copolymer consisting of a polycarbonate block represented by the following general formula [1] and a polydiorganosiloxane block represented by the following general formula [3], and (A-2) 100 parts by weight of a resin component (A component) consisting of 0 to 99 parts by weight of an aromatic polycarbonate resin consisting of a polycarbonate block represented by the following general formula [1], and (B) a polycarbonate resin composition containing 3.0 to 15.0 parts by weight of a (meth)acrylic-modified polyorganosiloxane (B component) obtained by graft copolymerizing a polyorganosiloxane (B1 component) represented by the following general formula [4] with a (meth)acrylic acid ester (B2 component). 【Chemistry 1】 [(In the above general formula [1], R 1 and R 2 each independently represents a group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 18 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 14 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxy group, and when there are a plurality of each of these groups, they may be the same or different, e and f each represent an integer of 1 to 4, and W represents a single bond or at least one group selected from the group consisting of groups represented by the following general formula [2]: 【Chemistry 2】 (In the above general formula [2], R 11 , R 12 , R 13 , R 14 , R 15 , R 16 , R 17 and R 18 each independently represents a group selected from the group consisting of a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, an aryl group having 6 to 14 carbon atoms, and an aralkyl group having 7 to 20 carbon atoms; R 19 and R 20 each independently represents a group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 10 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxy group, and when there are a plurality of groups, they may be the same or different, g is an integer from 1 to 10, and h is an integer from 4 to 7. 【Chemistry 3】 (In the above general formula [3], R 3 , R 4 , R 5 , R 6 , R 7 and R 8 are each independently a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 12 carbon atoms; R 9 and R 10 are each independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms, p is a natural number, q is 0 or a natural number, and the average chain length p+q is a natural number from 20 to 200. X is a divalent aliphatic group having 2 to 8 carbon atoms. 【Chemistry 4】 [In the above general formula [4], R 1 , R 2 and R 3 each independently represent a hydrocarbon group having 1 to 20 carbon atoms or a halogenated hydrocarbon group having 1 to 20 carbon atoms, and Y represents an organic group having at least one group selected from the group consisting of a vinyl group, an allyl group, and a γ-(meth)acryloxypropyl group, and an SH group. X 1 and X 2 each independently represent a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, or a group represented by SiR 4 R 5 R 6 (R 4 and R 5 each independently represent a hydrocarbon group having 1 to 20 carbon atoms or a halogenated hydrocarbon group having 1 to 20 carbon atoms, and R 6 represents a hydrocarbon group having 1 to 20 carbon atoms, a halogenated hydrocarbon group having 1 to 20 carbon atoms, or an organic group having at least one group selected from the group consisting of a vinyl group, an allyl group, and a γ-(meth)acryloxypropyl group, and an SH group), m is an integer from 1 to 10,000, n is an integer of 1 or more, and the siloxane chain may be branched.]

2. The polycarbonate resin composition according to claim 1, characterized in that p + q in the above formula [3] is 30 to 120.

3. 3. The polycarbonate resin composition according to claim 1, wherein the content of the polydiorganosiloxane block represented by the formula [3] in the component A-1 is 4 to 20% by weight.

4. 4. The polycarbonate resin composition according to claim 1, wherein the viscosity average molecular weight of component A-1 is 11,000 to 30,000.

5. 5. The polycarbonate resin composition according to any one of claims 1 to 4, wherein the polydiorganosiloxane block represented by the formula [3] is a polydiorganosiloxane block derived from a (2-allylphenol)-terminated polydiorganosiloxane or a (2-methoxy-4-allylphenol)-terminated polydiorganosiloxane.

6. R in the above formula [3] 3 , R 4 , R 5 , R 6 , R 7 and R 8 The polycarbonate resin composition according to any one of claims 1 to 5, wherein is a methyl group.

7. 7. The polycarbonate resin composition according to any one of claims 1 to 6, wherein the polycarbonate block represented by the formula [1] is a polycarbonate block derived from 2,2-bis(4-hydroxyphenyl)propane.

8. In the above formula [4], R 1 , R 2 , R 3 The polycarbonate resin composition according to any one of claims 1 to 7, wherein is a methyl group.

9. 9. The polycarbonate resin composition according to any one of claims 1 to 8, wherein component B2 is methyl methacrylate and / or 2-hydroxyethyl methacrylate.

10. A molded article formed from the polycarbonate resin composition according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • JP1961-007641B

  • Resin composition

    JP1988213555A

  • Resin composition

    JP1992136065A

  • Flame-retardant polycarbonate resin composition

    JP1997316320A

  • Flame-retardant thermoplastic polycarbonate composition, its use and method for producing the same

    JP2006052401A